PANDANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN TERHADAP PROFESI PENDIDIK - Kholidah, Neneng Rika Jazilatul; Saputri, Ernia Duwi (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractEducation is a very important field for human life. Education can encourage the improvementof human quality in the form of increasing cognitive, affective, and psychomotor competencies.The purpose of this study was to find out the views of students of Pancasila and citizenshipeducation programs on the teaching profession. This study was designed as a qualitativedescriptive study with a single embedded case study strategy. Data sources were obtained fromthe research subjects as follows; 1) Informants / Resource Persons, namely students of thePancasila and Citizenship Education Study Program; 2) Student activities when discussing theprofession of an educator. Data collection techniques used are in-depth interviews, directobservation and document analysis. The data validity technique uses standards of credibility,transferability and dependability and confirmation. Data analysis techniques use interactivemethods. The results of the study can be concluded that the views of students on the teachingprofession are teaching professionals is a respectable profession, the existence of the teachingprofession in the community according to students Educators are community teachers,educators as dampening conflicts of cultural differences and profiles of ideal educatorsaccording to students and reasons students view the teaching profession The ideal teacher doesnot have selfishness so the teacher can be said to be a teacher who is able to understand thewishes of students.Keywords: Views, Students, Professional Educators